DESIGNING ENGLISH VOCABULARY BOOKLET FOR MOTORCYCLE ENGINEERING DEPARTMENT OF VOCATIONAL HIGH SCHOOL - Rahmatika Kayyis; Kholifah (English Education Department, 2021)
In Vocational High School, the students mostly learn vocabulary from a general course book. However, the entire vocabulary that they learn is not related with the vocabulary that they will use in their future work field. The research aimed to find out the target needs, to describe the learning needs, and to develop an appropriate English vocabulary booklet for the students of the Motorcycle Engineering Study Program of SMK KH.Ghalib Pringsewu. The research is categorized as Research and Development (R&D) research design. A need analysis questionnaire is distributed to the students. Based on the result, 80% of the students need support for their future job including the need for learning English vocabulary to access the information correlates with their work. Meanwhile, 70% of students having lacks or difficulties in learning English materials such as in memorizing, expressing sentences, and reading the text because they do not understand the meaning of the word. Moreover, 76% of students want to learn English appropriate with their major equipped with media like a worksheet, used LCD, and the pictures with its meaning. The product designed consists of three small unit in the form of booklet including materials and exercises. After the writer draft of the materials was developed; the materials were then evaluated by experts’ judgment. Based on materials evaluation the main score of all aspects of developed materials was 3.35 which is categorized as “Very Good”.